Formulação e caracterização de pastas espumadas por incorporação de ar e estabilizantes minerais - Lima, Marco Antônio Batista de (2011)
Cementing operations may occur at various stages of the life cycle of an oil well since its construction until its definitive abandonment. There are some situations in which the interest zones are depleted or have low fracture pressure. In such cases, the adoption of lowdensity cement slurries is an efficient solution. To this end, there are basically three ways to reduce the density of cement slurries: using microspheres, water extending additives or foamed cement. The objective of this study is to formulate, to study and to characterize lowdensity foamed cement, using an air entrainment surfactant with vermiculite or diatomite as water extenders and stabilizers. The methodology consists on preparation and evaluation of the slurries under the American Petroleum Institute (API) and the Brazilian Association of Technical Standards (ABNT) guidelines. Based on calculated densities between 13 and 15 ppg (1.559 and 1.799 g/cm3), the slurries were prepared with fixed surfactant concentration, varying the concentrations of vermiculite and diatomite and were compared with the base slurries. The results of plastic viscosity, yield point and gel strength and the compressive strength for 24 h showed that the slurries presented suitable rheology and mechanical strength for cementing operations in oil wells, and had their densities reduced between 8.40 and 11.89 ppg (1.007 and 1.426 g/cm3). The conclusion is that is possible, under atmospheric conditions, to obtain light weighted foamed cement slurries with satisfactory rheological and mechanical properties by means of air entrainment and mineral additions with extenders and stabilizers effects. The slurries have great potential for cementing operations; applicability in deep wells, in low fracture gradient formations and in depleted zones and bring cost savings by reducing the cementing consumption